2017
DOI: 10.1002/cam4.1245
|View full text |Cite
|
Sign up to set email alerts
|

POLE somatic mutations in advanced colorectal cancer

Abstract: Despite all the knowledge already gathered, the picture of somatic genetic changes in colorectal tumorigenesis is far from complete. Recently, germline and somatic mutations in the exonuclease domain of polymerase epsilon, catalytic subunit (POLE) gene have been reported in a small subset of microsatellite‐stable and hypermutated colorectal carcinomas (CRCs), affecting the proofreading activity of the enzyme and leading to misincorporation of bases during DNA replication. To evaluate the role of POLE mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 25 publications
(40 reference statements)
0
28
0
Order By: Relevance
“…Germline and somatic POLE mutations are associated with hypermutated CRC and endometrial cancer. 32,33 Previous studies have also found that hypermutated MSS tumors harbored POLE mutations. 34,35 Four cases with hypermutated MSS tumors harboring POLE mutations were also observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Germline and somatic POLE mutations are associated with hypermutated CRC and endometrial cancer. 32,33 Previous studies have also found that hypermutated MSS tumors harbored POLE mutations. 34,35 Four cases with hypermutated MSS tumors harboring POLE mutations were also observed in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, some CRC patients (2-3%) harbor MSS tumors with DNA polymerase epsilon or delta (POLE, POLD) mutations. It has been reported that in a subset of MSS tumors, mutations in the genes encoding these enzymes responsible for DNA synthesis and repair (92,93) are associated with an ultramutated phenotype defined by a high number of frameshift mutations. Indeed, predicted neoantigen load is 3-4 times higher in MSS tumors carrying POLE mutations than in MSI CRCs (13,79).…”
Section: Immune Checkpoint Blockade In Crcmentioning
confidence: 99%
“…Interestingly, BRAF V600E mutations were commonly observed with MLH1 mutations in sporadic cases and with CIMP [ 60 , 61 ]. DNA polymerase epsilon ( POLE ) mutations have been observed in a small subset of microsatellite-stable and hypermutated CRCs that affects the proofreading activity of the enzyme, leading to the misincorporation of the bases during DNA replication [ 62 ]. According to the TCGA study, ACVR2A , APC , TGFβ-R2 , MSH3 , MSH6 , SLC9A9 , TCF7L2 , and BRAFV600E are the most frequently mutated genes in these hypermutated tumors [ 44 ].…”
Section: Molecular Biology and Genetic Perspectivementioning
confidence: 99%